The Effects of Zinc-biocomplex and Zinc-methionate supplementation on the ration for lambs - Supriyati . (Jurnal Ilmu Ternak dan Veteriner, 2008)
The effects of zinc-biocomplex and zinc-methionate on the growth of young sheep were studied in this trial. Eighteen young male local sheeps were grouped into 3 groups based on body weight. The treatments are: R1 (Control), R2 (R1 + Zn-biocomplex supplementation), R3 (R1 + Zn-methionate supplementations), with the concentration of Zn was 50 mg kg-1 in daily concentrate.  Zink biocomplex and methionate were prepared in IRIAP laboratory. Feeds given were Elephant grass ad libitum and 200 g h-1 concentrate (CP = 15.40%). The initial body weights were 12.36 to 12.97 kg. Body weights were measured every forthnight and feed consumption was recorded daily. Completely randomized design was applied in this trial. Statistical analysis was carried out by using General Linear Model (GLM). After 3 months feeding trial the average daily gains were 52.65, 71.28 and  71.30 g h-1 (P<0.05) for treatments R1, R2 and R3, respectively; with the mean daily intakes were 583, 562 and 531 g h-1 (P<0.05). The mean feed conversion ratio (FCR) for R1, R2 and R3 were 10.96, 8.44 dan 8.75 (P<0.05). It could be concluded that supplementation of Zn biocomplex and methionate produced in this institute (R1 and R2) gave better performance than control. Forms of Zn (biocomplex and methionate) did not give significant effect on difference (P>0.05) growth. Key Words: Zn- Biocomplex, Zn-Methionate, Supplementation, Growth, Sheep